Isolation and identification of Cr-resistant bacteria from the rhizosphere of Tagetes sp. and their ability to reduce Cr(VI) - VINCENTIA IRENE MEITINIARTI; ELSA KRISTIANI PUTRI; ATHALIA EUGENIA RUNTU; RULLY ADI NUGROHO; SRI KASMIYATI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Meitiniarti VI, Putri EK, Runtu AE, Nugroho RA, Kasmiyati S. 2022. Isolation and identification of Cr-resistant bacteria from the rhizosphere of Tagetes sp. and their ability to reduce Cr(VI). Biodiversitas 23: 4118-4124. Bioremediation involving the interaction of plants with microorganisms is a technique for improving the environment polluted with chromium hexavalent [Cr(VI)]. Marigolds (Tagetes sp.) are known to be a hyperaccumulator plant for Cr(VI) and there are microbes in its rhizosphere that enable the plant tolerant to heavy metals. The aims of this study were to isolate and identify indigenous rhizobacteria resistant to Cr(VI) from Tagetes sp. and to test the ability of these bacterial isolates to reduce Cr(VI). Three isolates of Cr(VI) resistant bacteria were obtained in this study, namely Micrococcus luteus RT-9, Stenotrophomonas maltophilia RT-12, and Brevundimonas sp. RT-23. M. luteus RT-9 and S. maltophilia RT-12 which were resistant to Cr(VI) 100 mg L-1 and their mixture were tested for their ability to reduce Cr(VI) in a liquid medium. Microbacterium sp. SpR3 obtained by the previous study was used as a reference. The results showed that the isolate of S. maltophilia RT-12 had a higher ability (2.2 mg L-1 h-1) than M. luteus RT-9 (0.9 mg L-1 h-1). S. maltophilia RT-12 had the ability to reduce Cr(VI) similar to Microbacterium sp. SpR3. The mixed inoculation of M. luteus RT-9, S. maltophilia RT-12, and Microbacterium sp. SpR3 did not show a difference in the reduction ability of Cr (VI) compared to pure cultures.